American Kingship? Monarchical Origins of Modern Presidentialism. - Scheuerman, William E. (2013)
The modern obsession with executive charisma, especially in the context of the presidentialism variety of liberal democracy, is commonplace. This obsession derives from the oftentimes overlooked monarchical origins of the modern presidential executive. The presidential executive is outfitted with some of the awesome powers of European kingship, but it is no longer able to justify those powers on the basis of traditional religious ideas. Charisma serves as a functional replace for religiously inspired ideas of divine monarchy. Special attention is paid to the role of Alexander Hamilton in the transformation of traditional monarchist political theory into the theoretical underpinnings of the American presidency.